The potential of increasing man-made air pollution to reduce rainfall over southern West Africa - Pante, Gregor; Knippertz, Peter; Fink, Andreas H.; Kniffka, Anke (Atmospheric Chemistry and Physics, 2021)
Abstract. Southern West Africa has one of the fastest-growing populations worldwide. This has led to a higher water demand and lower air quality. Over the last 3 decades, most of the region has experienced decreasing rainfall during the little dry season (LDS; mid-July to end of August) and more recently also during the second rainy season (SRS; September–October), while trends during the first rainy season (FRS; mid-May to mid-July) are insignificant. Here we analyse spatio-temporal variations in precipitation, aerosol, radiation, cloud, and visibility observations from surface stations and from space to find indications for a potential contribution of anthropogenic air pollution to these rainfall trends. The proposed mechanism is that the dimming of incoming solar radiation by aerosol extinction contributes to reducing vertical instability and thus convective precipitation. To separate a potential aerosol influence from large-scale climatic drivers, a multilinear-regression model based on sea-surface temperature (SST) indices is used. During both LDS and SRS, weakly statistically significant but accelerating negative rainfall trends unrelated to known climatic factors are found. These are accompanied by a strong increase in pollution over the upstream tropical Atlantic caused by fire aerosol from Central Africa, particularly during the LDS. Over southern West Africa, no long-term aerosol records are available, inhibiting a direct quantification of the local man-made effect. However, significant decreases in horizontal visibility and incoming surface solar radiation are strong indicators for an increasing aerosol burden, in line with the hypothesized pollution impact on rainfall. The radiation trend is further enhanced by an increase in low-level cloudiness. The large spatial extent of potentially aerosol-related trends during the LDS is consistent with the stronger monsoon flow and less wet deposition during this season. Negligible aerosol impacts during the FRS are likely due to the high degree of convective organization, which makes rainfall less sensitive to surface radiation. The overall coherent picture and the accelerating trends – some of which are concealed by SST effects – should alarm policymakers in West Africa to prevent a further increase in air pollution as this could endanger water supply and food and energy production for a large and growing population.
openalex: W3118764838 mag: 3118764838
Keywords: openalex:import

Increasing manmade air pollution likely to reduce rainfall in southern West Africa - Pante, Gregor; Knippertz, Peter; Fink, Andreas H.; Kniffka, Anke (2020)
Abstract. Southern West Africa has one of the fastest growing populations worldwide. This has led to a higher water demand and lower air quality. Over the last three decades, most of the region has experienced decreasing rainfall during the little dry season (LDS, mid-July to end of August) and more recently also during the second rainy season (SRS, September–October), while trends during the first rainy season (FRS, mid-May to mid-July) are insignificant. Here we use spatio-temporal variations of precipitation, radiation, cloud and visibility observations from surface stations and from space to investigate whether the increased pollution has contributed to suppressing rainfall by dimming incoming solar radiation. To isolate a potential aerosol influence, a multi-linear regression model based on sea-surface temperature (SST) indices is used. During both LDS and SRS weakly statistically significant but accelerating negative rainfall trends unrelated to known climatic factors are found. These are accompanied by a strong increase of pollution over the upstream tropical Atlantic caused by fire aerosol from Central Africa, particularly during the LDS. Over southern West Africa, where no long-term aerosol records are available, significant decreases in horizontal visibility and incoming surface solar radiation are consistent with the hypothesized pollution impact. The latter trend is further enhanced by an increase in low-level cloudiness. The larger spread of potentially aerosol-related effects during the LDS is consistent with the stronger monsoon flow and less wet deposition. Negligible aerosol impacts during the FRS are likely due to the high degree of convective organization, which makes rainfall generation less sensitive to surface radiation. The overall coherent picture and the accelerating trends – some of which concealed by SST effects – should alarm policymakers in West Africa to prevent a further increase in air pollution, as this could endanger water supply, and food and energy production for a large and growing population.
openalex: W3028950417 mag: 3028950417
Keywords: openalex:import

Increasing man-made air pollution reduces rainfall in southern West Africa - Pante, Gregor; Knippertz, Peter; Fink, Andreas H.; Kniffka, Anke (2020)
openalex: W3124702143 mag: 3124702143
Keywords: openalex:import

Pollution slightly enhances atmospheric cooling by low-level clouds in tropical West Africa - Hahn, Valerian; Meerkötter, R.; Voigt, Christiane; Gisinger, Sonja; Sauer, Daniel; Catoire, Valéry; Dreiling, V.; Coe, Hugh; Flamant, Cyrille; Kaufmann, Stefan H. E.; Kleine, Jonas; Knippertz, Peter; et al. (Atmospheric Chemistry and Physics, 2023)
Abstract. Reflection of solar radiation by tropical low-level clouds has an important cooling effect on climate and leads to decreases in surface temperatures. Still, the effect of pollution on ubiquitous tropical continental low-level clouds and the investigation of the related impact on atmospheric cooling rates are poorly constrained by in situ observations and modeling, in particular during the West African summer monsoon season. Here, we present comprehensive in situ measurements of microphysical properties of low-level clouds over tropical West Africa, measured with the Deutsches Zentrum für Luft- und Raumfahrt (DLR) aircraft Falcon 20 during the DACCIWA (Dynamics–Aerosol–Chemistry–Cloud Interactions in West Africa) campaign in June and July 2016. Clouds below 1800 m altitude, identified as boundary layer clouds, were classified according to their carbon monoxide (CO) pollution level into pristine and less polluted clouds (CO < 135 ppbv) and polluted low-level clouds (CO > 155 ppbv) as confirmed by the linear CO to accumulation aerosol number concentration correlation. Whereas slightly enhanced aerosol background levels from biomass burning were measured across the entire area, clouds with substantially enhanced aerosol levels were measured in the outflow of major coastal cities, as well as over rural conurbations in the hinterlands. Here we investigate the impact of pollution on cloud droplet number concentration and size during the West African monsoon season. Our results show that the cloud droplet number concentration (CDNC) measured in the size range from 3 to 50 µm around noon increases by 26 % in the elevated aerosol outflow of coastal cities and conurbations with elevated aerosol loadings from median CDNC of 240 cm−3 (52 to 501 cm−3 interquartile range) to 324 cm−3 (60 to 740 cm−3 interquartile range). Higher CDNC resulted in a 17 % decrease in effective cloud droplet diameter from a median deff of 14.8 µm to a deff of 12.4 µm in polluted clouds. Radiative transfer simulations show a non-negligible influence of higher droplet number concentrations and smaller particle sizes on the diurnally averaged (noon) net radiative forcing at the top of atmosphere of −3.9 W m−2 (−16.3 W m−2) of polluted with respect to less polluted clouds and lead to a change in instantaneous heating rates of −22.8 K d−1 (−17.7 K d−1) at the top of clouds. Thus, the atmospheric cooling by low-level clouds increases only slightly in the polluted case due to the already elevated background aerosol concentrations. Additionally, the occurrence of mid- and high-level cloud layers atop buffer this effect further, so that the net radiative forcing and instantaneous heating rate of low-level clouds turn out to be less sensitive towards projected future increases in anthropogenic pollution in West Africa.
openalex: W4385447801
Keywords: openalex:import